SINXRON TARJIMONLIKDA GRAMMATIKANING O’RNI («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
In this article, the concepts of grammar and simultaneous translation are classified and the interrelationship between them is explained through various examples.
Keywords: grammar, simultaneous translation, translation, oral translation.